Case study on venture capital financing of deep tech startups - Křížek, Tom; Svačina, Pavel, 1979-; Kovalčík, Martin; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This thesis investigates the transformation of deep-tech ideas into fundable ventures, addressing the question: 'How and why does an idea become a fundable deep-tech startup?' Utilizing a Most Different Systems Design, the study analyses three ventures—Sophomer, CasInvent Pharma, and Lam-X—that, despite differing in their technological origins and market strategies, all achieved external venture capital investment within the IOCB innovation ecosystem. The analysis reveals that a recurring configuration of three factors explains their first venture capital investment: Technology & IP, Team, and Demonstrated Traction. Technology & IP and Team emerge as foundational driving forces, providing a robust intellectual asset and capable leadership with business or industrial experience, respectively. Demonstrated Traction, in turn, serves as the critical de-risking signal that bridges the information asymmetry with investors, even as its specific form varies by case. This research suggests that the interplay and sequencing of these three factors constitute a core causal pathway to fundability in Czech biotechnology ecosystem.
Vedoucí práce: Pavel Svačina
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance a oceňování podniku [obor dipl. práce]; diplomové práce; master's theses